PERBANDINGAN SUHU LINGKUNGAN DAN PENGARUH PAKAN TERHADAP PRODUKTIVITAS SAPI PERAH DI DAERAH DENGAN KETINGGIAN BERBEDA - Dela Heraini; Bagus Priyo Purwanto; Suryahadi Suryahadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
This study was done to compare the environmental temperature and the effect of feed  management on dairy cattle productivity in KUTT Suka Makmur Grati Pasuruan. Primary data were collected by questionare based interview to the farmers at different height areas those were 40 farmers in lowland area and 40 farmers in highland area. Data were analyzed using descriptive statistics and quant itative methods. The results showed that temperatures in the lowlands were higher at around 24oC - 27oC, so cattle experiencing heat stress and the impact  was cattle consumed less feed, while the availability of  water was limited. In contrast, the highlands temperature was relatively low, about 22oC - 24oC. The cattle in highland was fed with elephant grass with a good nutrient content, so the cattle was able to produced well.  Keywords: Dairy Cattle, Environment, Feed Effect, Productivity, Temperature